Sharing information of urological cancer patient in terminal stage using Cybozulive® for home medical care - Yumura, Yasushi (Hinyokika kiyo. Acta urologica Japonica, 2014)
It is very important to share patient information because home patient care involves several different specialties of care. We introduced Cybozulive ® , a cloud-based free groupware, for 14 terminal-stage patients with urological cancer to share information among doctors and co-medical staff. This system enables access to patient information regardless of time and place. Of the 14 patients (mean age 74.4 years), 11 died of cancer. The average period in which Cybozulive® was used for the patients was 210 days. The average number of entries to the electronic bulletin board in this period was 88.4. We were able to obtain more information about the patients from the website. There was no difference in the average number of times that the patient consulted the out patient clinic before and after the introduction of Cybozulive® (before 7.0 ; after 6.3). After introduction of this system, eleven patients were hospitalized in our department 21 times. Eighteen of these 21 times, since we had acquired patient information from the website beforehand, there was a quick response for management of the emergency admission. This system could be used to construct a network for home care and may be helpful for sharing patient information in homecare